Investigation Of Microbiological Concentration In Indoor Air At School Classrooms - Wan Mohd Ali, Wan Norfazlinda (Universiti Sains Malaysia, 2018)
People spend most of their lifetime indoor whether residences, offices, schools, hospital and vehicles. Indoor air pollution is one of the most harmful environmental factors for human health. This study investigates the level of concentration of bacterial at four different school classrooms and determined the relationship of bacteria with temperature and relative humidity in Penang, Malaysia. The concentration of bacterial was determined using settle plate method. The agar media used was Nutrient Agar that were exposed to the atmosphere for 15 minutes at selected points in each school classrooms. The total of mean bacterial count for each school was 322.39 cfu/m3, 684.89 cfu/m3, 671 cfu/m3 and 387.44 cfu/m3 for SK Bayan Lepas, SK Tasek Gelugor, SMK Mutiara Impian and SK Machang Bubok, respectively. This study has shown that the temperature and relative humidity affect the bacterial counts. To conclude, activities from occupancy influence the bacterial count in selected schools in Penang.